Photographic Analysis of Aesthetically Pleasant Facial Profile in Aryan Group of Nepalese Population - Karki, Angelika (Europasian Journal of Medical Sciences, 2020)
Background: Facial aesthetics has been considered as the most significant factor for individual. The aim of the study was to identify the standard linear and angular measurement of facial profile in Aryan group of Nepalese population so as to set up aesthetic treatment goal. Methods: A cross-sectional observational study was done in fifty-seven subjects (27: females and 30: males, from 17-30 years). The landmarks were marked and two most commonly used lines were taken as reference lines E-line and S-line and seven facial angles were measured: Total Facial Convexity Angle (G-Prn-Pog), Facial Convexity Angle (G-Sn-Pog), Nasofacial Angle (G-Pog-N-Prn), Nasolabial Angle (Ls-Sn-Cm), Mentolabial Angle (Pog- B-Li),Nasofrontal Angle (G-N-Nd) and Nose tip Angle (N-Prn-Cm).Data was analyzed using Statistical Package for the Social Sciences (SPSS) 21. To assess anterior-posterior relationship of upper and lower lips judged by E-line and S-line were determined using correlation co-efficient (r). Likewise, to compare the angular measurement between males and females were determined using Mann-Whitney U test. Result: The anterior-posterior position of upper lip and lower lip judged by E-line were -3.78±0.67 mm and -1.92±0.61 mm respectively whereas upper and lower lips judged by S-line were 0.18±0.58 mm and 0.06±0.44 mm respectively. Statistically significant (p<0.001) strong correlation(r) was found between upper lip to E-line and S-line (0.999) and between lower lip to E-line and S-line. Out of seven angular parameters, four parameters showed gender dimorphism which means statistically significant difference (p<0.001) were seen in Nasofrontal Angle. Conclusion: Either one of the reference line can be used for evaluation of facial profile at the time of diagnosis. The parameters calculated by photographic analysis serve as a comparing guide for setting up aesthetic treatment plan and can be used both before and after orthodontic treatment.